Biodiversity friend or foe: land use by a top predator, the dingo in contested landscapes of the Australian Wet Tropics. (25th August 2016) - Morrant, Damian S.; Johnson, Christopher N.; Butler, James R. A.; Congdon, Bradley C.
Abstract: Dingoes ( Canis dingo ) in the coastal lowlands of Australia's Wet Tropics are perceived as a major threat to biodiversity and subjected to broad‐spectrum lethal control. However, evidence of their impacts is equivocal, and control programmes generally ignore the ecological benefits that dingoes might provide. Previous diet analysis has shown that dingoes in the Wet Tropics primarily prey on common, terrestrial mammals. However, little is known of dingo habitat use or prey acquisition in the region despite these activities having major implications for biodiversity conservation. We investigated land use by dingoes in the lowland Wet Tropics to enable predictions of potential prey types, relative prey use and modes of prey acquisition. Nine dingoes were tracked for 3–6 months. Home ranges and resting areas were estimated using multiple estimators, and habitat use was analysed using compositional analysis of habitat use and generalized additive models. Dingo ranging behaviour suggested that anthropogenic food subsidies were infrequently used. Each territory comprised several sclerophyll forest rest areas with adjacent sugarcane‐grassland high activity areas. Individuals used each rest‐activity area for extended durations before moving on to another. Sclerophyll and rainforests, which contain the fauna species of primary conservation concern, were generally used for rest/sleep, or movement between rest‐activity areas. Activity patterns were consistent with dingoes hunting in open sugarcane‐grassland habitats during daylight hours. Dingo activity was low in areas where fauna species of conservation concern occur, which suggests that dingoes do not pose a threat to their survival. Consequently, current broad‐spectrum lethal control may have minimal benefits or even incur costs for biodiversity. Maximizing the ecosystem services provided by dingoes while simultaneously minimizing their negative impacts requires a more targeted location‐specific management approach, one that assesses and mitigates impacts specifically where background circumstances suggest particular packs may be either a conservation or economic threat.